Science of the rice plant: Morphology - Science of the rice plant: Morphology (Food and Agriculture Policy Research Center, 1993)
This process has greatly contributed to the development of rice-based agriculture in Japan. It may be said, therefore, that the distinctive characteristic of rice research activities in Japan is represented by the closely interrelated development in the two fields: Production technologies and scientific studies